2016
DOI: 10.1016/j.ymeth.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Light-up and FRET aptamer reporters; evaluating their applications for imaging transcription in eukaryotic cells

Abstract: The regulation of RNA transcription is central to cellular function. Changes in gene expression drive differentiation and cellular responses to events such as injury. RNA trafficking can also have a large impact on protein expression and its localization. Thus, the ability to image RNA transcription and trafficking in real time and in living cells is a worthwhile goal that has been difficult to achieve. The availability of “light-up” aptamers that cause an increase in fluorescence of their ligands when bound b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…PFP-DFHBI exhibits 5-fold higher binding affinity to Spinach2 than DFHBI. Therefore, Spinach2-PFP-DFHBI shows 3–4-fold brighter fluorescence and less salt concentration dependency 58 . TO1 can greatly enhance its fluorescence by binding to G4 quadruplexes containing aptamers.…”
Section: Probes Imaging Exogenous Rnasmentioning
confidence: 93%
See 1 more Smart Citation
“…PFP-DFHBI exhibits 5-fold higher binding affinity to Spinach2 than DFHBI. Therefore, Spinach2-PFP-DFHBI shows 3–4-fold brighter fluorescence and less salt concentration dependency 58 . TO1 can greatly enhance its fluorescence by binding to G4 quadruplexes containing aptamers.…”
Section: Probes Imaging Exogenous Rnasmentioning
confidence: 93%
“…(b) Chemical structures of fluorophores in the RNA aptamer/fluorophore systems: DFHBI, DFHBI-1T 57 , PFP-DFHBI 58 , TO1 56 .…”
Section: Figmentioning
confidence: 99%
“…4) The aptamers should be tested for their abilities to bind ligand under similar conditions as present in the cytoplasm in which the free Mg 2+ concentration is much lower than is used for selecting most aptamers and where the major monovalent cation is K + rather than Na + . We have found that aptamer affinities and ligand specificities can be quite different in buffers that approximate intracellular conditions compared with the buffers in which they were selected (Muslum Ilgu, et al, 2016; M. Ilgu, Wang, Lamm, & Nilsen-Hamilton, 2013).…”
Section: Imagetagsmentioning
confidence: 99%
“…Instead, we created IMAGEtags consisting of multiple copies of the same aptamer sequence in strings of at least five units. These IMAGEtags function well for imaging promoter activity when the aptamer ligand is presented in two forms, each conjugated with one of a FRET pair (Muslum Ilgu et al, 2016; Shin et al, 2014). The effectiveness of these single-aptamer IMAGEtags can be understood when it is considered that, when an internal aptamer of the string binds one of the two ligands, there is a 50% chance that one or the other adjacent aptamer will bind the FRET pair and therefore a 75% chance that the central aptamer will have an adjacent FRET partner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation